2009
DOI: 10.1007/s00520-009-0763-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of HCV infection in childhood cancer survivors

Abstract: The outcome of hepatitis C in our patients is comparable to the one described in European cohorts of adult cancer survivors and perinatally infected subjects. Nevertheless, progression to high degrees of hepatic damage has to be monitored by a careful follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In our study (paper II) all HCV infected patients, transfused during treatment of childhood cancer, had mild to moderate liver fibrosis, albeit the long duration of infection and previous chemo-and immunosuppressive therapy, which has been shown to increase the risk of liver fibrosis (27). Our results are in line with some of the previous long-term studies on childhood cancer survivors (26,29,128), however Castellino et al described a high prevalence of 13 % liver cirrhosis already after 12 years of median infection duration (27).…”
Section: 15( Natural(coursesupporting
confidence: 93%
“…In our study (paper II) all HCV infected patients, transfused during treatment of childhood cancer, had mild to moderate liver fibrosis, albeit the long duration of infection and previous chemo-and immunosuppressive therapy, which has been shown to increase the risk of liver fibrosis (27). Our results are in line with some of the previous long-term studies on childhood cancer survivors (26,29,128), however Castellino et al described a high prevalence of 13 % liver cirrhosis already after 12 years of median infection duration (27).…”
Section: 15( Natural(coursesupporting
confidence: 93%
“…Similar course and progression of HCV were seen in pediatric patients with a history of malignancies, with about 20% of patients demonstrating spontaneous clearance and up to 5% of patients showing progression to cirrhosis [17,18].…”
Section: Clinical Coursesupporting
confidence: 52%
“…A select subset of our study population underwent liver biopsy, the most accurate diagnostic measure of cirrhosis, and thus outcome status may be misclassified for the subset of survivors who underwent liver imaging (sensitivity=68%, specificity=88% compared with liver biopsy) (20), or no assessment because symptoms of cirrhosis were not clinically apparent. This misclassification would underestimate the cumulative incidence of cirrhosis in our study and prior studies (16, 17) given the use of similar approaches for outcome classification. Furthermore, given lack of information about age at HCV exposure for survivors with non-transfusion acquired HCV, age at HCV exposure for these individuals was defined as time of cancer diagnosis, which may be inaccurate.…”
Section: Discussionmentioning
confidence: 56%
“…For example, a study of 31 HCV-seropositive pediatric cancer survivors in Egypt reported no cases of cirrhosis with a mean follow-up of 2.6 years (15). Using information reported in a multi-institution cohort study of 105 HCV-seropositive pediatric cancer survivors in Italy and Austria (16), the estimated incidence proportion of cirrhosis was 0.95% (95% CL: 0.02%, 5.2%) with a median follow-up of 18 years. The incidence proportion of cirrhosis estimated in a separate study of 77 HCV-seropositive pediatric cancer survivors in Italy (17) was 5.2% (95% CL: 1.4%, 13%) with a median follow-up of 21 years.…”
Section: Discussionmentioning
confidence: 99%